STUDY ON WET PROCESSING OF BLOCK CHILLY - Dwi Dian Praptanto; Kurnia Herlina Dewi; Bosman Sidebang (BPFP Faperta UNIB, 2013)
The purpose of this study is to examine the effect of drying time in weight and water content, combination effect of drying time and size of the material, and consumer acceptance to the product in the wet processing of chili blocks production. Method used in the research is completely randomized design (CRD) with two factorials are material size and drying time. Data were analyzed using ANOVA and further analysis using DMRT at 5% significance level. Organoleptic test result was analyzed using the Kruskal-Wallis and Tukey test for further analysis. Application of the equal drying time to two different size of material: rough and finest block chili, showed the result that water content of the rough block chili is lower than the finest block chilli. Application of the different drying time duration to the same size of chili showed the lower water content with increasing duration of drying time. The water content of the material tends to decrease with increasing duration of drying time. The level of consumer’s preferences to the product of wet processing of chili blocks production is equal for scents, but it’s different for color, texture and overall preferences.